Implementation of School Culture in Improving Religious Character in Islamic Boarding Schools - Achmad Qusyairi Mahfudi; Moh. Rifa’i (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to examine the implementation of school culture in supporting the improvement of students' religious character building in pesantren-based schools and identify the strategies and elements of school culture. Based schools, as well as identifying the most effective strategies and elements of school culture in integrating academic achievement with most effective in integrating academic achievement with Islamic values. The approach used is qualitative, with data collection techniques in the form of observation, in-depth interviews, and documentation. The research informants comprised principals, teachers, students, and other related parties involved in implementing school culture and the implementation of school culture. Data analysis was conducted by using the interactive model of Miles, Huberman, and Saldana through stages of data reduction, data presentation, and conclusion drawing. Results The results showed that the three primary forms of school culture that proved effective in shaping students' religious character are the recitation of the Qur'an before teaching and learning activities, yellow book studies, and mujahadah and prayer together. Together. These three activities are routinely structured and sustainably to form a religious habitus. Continuously forming a religious habitus in students' daily lives. Students' daily lives. This finding provides a strategic contribution for pesantren-based schools in strengthening character education based schools in strengthening character education while supporting academic achievement that is aligned with Islamic values